Involvement of aryl hydrocarbon receptor in the aflatoxin B1 and fumonisin B1 effects on in vitro differentiation of murine regulatory-T and Th17 cells - Mary, Verónica Sofía (2024)
Impact Factor (IF). 2022: 5.8